Cluj: A Jesuit Educational Outpost in Transylvania, 1693-1773 - Shore, Paul (Catholic Education: A Journal of Inquiry and Practice, 2001)
For the 80 years the Society of Jesus operated a complex of institutions in the Transylvanian town of Cluj, including an academy, a school for aristocratic boys, a residence, and an architecturally distinguished church. The Jesuits endeavored to convert the local population, which included Orthodox Romanians, Jews, Roma (Gypsies), Armenians, Lutherans, and Unitarians, to Catholicism and to introduce the program of studies outlines in their curricular guide, the Ratio Studiorum. While their conversion efforts met with only modest success, the Jesuits had a major impact on the culture of the region, training the local elites, introducing the Baroque aesthetic in the visual arts, operating a printing press and pharmacy, and employing outstanding scientists as teachers. The reasons for the failure of the Jesuits to make more progress in their missionary efforts may be found in both local circumstances and in the institutional culture of the Society itself. Political forces beyond the control of the Society sealed its fate, and it was suppressed by order of the pope in 1773. The vestiges of the Jesuit era in Cluj, however, are still visible today.